(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The role of teacher has considerable significant at all levels of education i.e. primary, secondary and higher. In a school at primary level the teacher’s role is considered with the socialization processes which are followed at a letter stage by the fundamental skills of literacy. At secondary level the focus shift towards instruction and the assessment of performance which assumes even greater significance at the higher educational level. The teacher’s role at all level is important. This role is however, is constrained by a number of maters, reasons and problems. The teachers have to face May pressures at personal and work related levels. This article focus on teacher effectiveness, qualities of effectiveness teachers and model of teacher effectiveness.